Effect of a low versus intermediate tidal volume strategy on pulmonary complications in patients at risk of acute respiratory distress syndrome—a randomized clinical trial - de Haro, Candelaria; Neto, Ary Serpa; Gomà, Gemma; González, Maria Elena; Ortega, Alfonso; Forteza, Catalina; Frutos-Vivar, Fernando; García, Raquel; Simonis, Fabienne D.; Gordo-Vidal, Federico; Suarez, David; Schultz, Marcus J.; et al. (Frontiers in Medicine, 2023)
Introduction There is no consensus on whether invasive ventilation should use low tidal volumes (VT) to prevent lung complications in patients at risk of acute respiratory distress syndrome (ARDS). The purpose of this study is to determine if a low VT strategy is more effective than an intermediate VT strategy in preventing pulmonary complications. Methods A randomized clinical trial was conducted in invasively ventilated patients with a lung injury prediction score (LIPS) of >4 performed in the intensive care units of 10 hospitals in Spain and one in the United States of America (USA) from 3 November 2014 to 30 August 2016. Patients were randomized to invasive ventilation using low VT (≤ 6 mL/kg predicted body weight, PBW) (N = 50) or intermediate VT (> 8 mL/kg PBW) (N = 48). The primary endpoint was the development of ARDS during the first 7 days after the initiation of invasive ventilation. Secondary endpoints included the development of pneumonia and severe atelectases; the length of intensive care unit (ICU) and hospital stay; and ICU, hospital, 28– and 90–day mortality. Results In total, 98 patients [67.3% male], with a median age of 65.5 years [interquartile range 55–73], were enrolled until the study was prematurely stopped because of slow recruitment and loss of equipoise caused by recent study reports. On day 7, five (11.9%) patients in the low VT group and four (9.1%) patients in the intermediate VT group had developed ARDS (risk ratio, 1.16 [95% CI, 0.62–2.17]; p = 0.735). The incidence of pneumonia and severe atelectasis was also not different between the two groups. The use of a low VT strategy did neither affect the length of ICU and hospital stay nor mortality rates. Conclusions In patients at risk for ARDS, a low VT strategy did not result in a lower incidence of ARDS than an intermediate VT strategy. Clinical Trial Registration: ClinicalTrials.gov, identifier NCT02070666.